Mathematical Association of America
Mathematical Association of America
Mathematical Association of America
Reviewed work(s):
Source: The American Mathematical Monthly, Vol. 119, No. 4 (April 2012), pp. 344-351
Published by: Mathematical Association of America
Stable URL: http://www.jstor.org/stable/10.4169/amer.math.monthly.119.04.344 .
Accessed: 21/09/2012 22:53
Your use of the JSTOR archive indicates your acceptance of the Terms & Conditions of Use, available at .
http://www.jstor.org/page/info/about/policies/terms.jsp
.
JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of
content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms
of scholarship. For more information about JSTOR, please contact support@jstor.org.
Mathematical Association of America is collaborating with JSTOR to digitize, preserve and extend access to
The American Mathematical Monthly.
http://www.jstor.org
PROBLEMS AND SOLUTIONS
Edited by Gerald A. Edgar, Doug Hensley, Douglas B. West
with the collaboration of Mike Bennett, Itshak Borosh, Paul Bracken, Ezra A. Brown,
Randall Dougherty, Tamás Erdélyi, Zachary Franco, Christian Friesen, Ira M. Ges-
sel, László Lipták, Frederick W. Luttmann, Vania Mascioni, Frank B. Miles, Bog-
dan Petrenko, Richard Pfiefer, Cecil C. Rousseau, Leonard Smiley, Kenneth Stolarsky,
Richard Stong, Walter Stromquist, Daniel Ullman, Charles Vanden Eynden, Sam Van-
dervelde, and Fuzhen Zhang.
PROBLEMS
11635. Proposed by Marian Tetiva, National College “Gheorghe Roşca Codreanu”,
Bârlad, Romania, and Nicuşor Minculete, “Dimitrie Cantemir” University, Braşov,
Romania.
(a) Let α and β be distinct nonzero real numbers. Let a, b, c, x, y, z be real, with
0 < a < b < c and a ≤ x < y < z ≤ c. Prove that if
x α + y α + z α = a α + bα + cα and x β + y β + z β = a β + bβ + cβ
then x = a, y = b, and z = c.
(b) Let α1 , α2 , α3 be distinct nonzero real numbers. Let a1 , a2 , a3 , a4 , x1 , x2 , x3 , x4 be
real, with 0 < a1 < a2 < a3 < a4 and a1 ≤ x1 < x2 < x3 < x4 ≤ a4 . If
4 4
X α X α
xk j = ak j
k=1 k=1
SOLUTIONS
and hence
Solution to Part (b) by Richard Stong, Center for Communications Research, San
Diego, CA. The largest such value of p is 2. For p = 2, we have 2(A2 + B 2 ) − (A +
B)2 = (A − B)2 ; hence the expression is always positive semidefinite. For larger odd
p, take A = −I and B = 0. Now 2 p−1 (A p + B p ) − (A + B) p = −(2 p−1 − 1)I , and
the expression is not positive semidefinite.
For larger even p, let x be a small positive number, and take A = 10 00 and B =
0 x
. Note that A p = A and B p = x p I . Let a p be the (2, 2)-entry of (A + B) p . Note
x 0
that a0 = 1, a1 = 0, and a p = a p−1 + x 2 a p−2 for p ≥ 2. Hence a p = x 2 + O(x 4 ).
Thus the (2, 2)-entry of 2 p−1 (A p + B p ) − (A + B) p is −x 2 + O(x 4 ), and the matrix
is not positive semidefinite.
Also solved by J. Grivaux (France), O. Kouba (Syria), J. H. Lindsey II, J. Simons (U. K.), and the proposers.
Twisted Semigroups
11490 [2010, 278]. Proposed by Gábor Mészáros, Kemence, Hungary. A semigroup S
agrees with an ordered pair (i, j) of positive integers if ab = b j a i whenever a and b
are distinct elements of S. Find all ordered pairs (i, j) of positive integers such that if
a semigroup S agrees with (i, j), then S has an idempotent element.
Solution by Nicolás Caro, Colombia. The required pairs are all pairs other than (1, 1).
Let (i, j) be a pair of positive integers, and let S be a semigroup agreeing with (i, j)
that has no idempotent elements. For k ≥ 0 and x ∈ S, we have x x 2 x k = (x 2 ) j x i x k
A Matrix-Sum Inequality
11496 [2010, 370]. Proposed by Benjamin Bogoşel (student), West University of
Timisoara, Timisoara, Romania, and Cezar Lupu (student), University of Bucharest,
Bucharest, Romania. For a matrix X with real entries, let s(X ) be the sum of its
entries. Prove that if A and B are n × n real matrices, then
n s(A A T )s(B B T ) − s(AB T )s(B A T ) ≥
Solution by Richard Stong, Center for Communications Research, San Diego, CA. The
required inequality has been corrected above; there was an extra “+” within the first
term, and A T B was printed instead of B A T .
Let 1 be the column vector with each entry 1, so s(X ) = 1T 1. For n × n matrices
A, B, and C, let
T
1 A
M = 1T B ;
1T C
note that M is a 3 × n matrix. Also,
s(A A T ) s(AB T ) s(AC T )
Now ab/2, bc/2, cd/2, da/2 are the areas of AOB, BOC, COD, DOA, so this is the
desired result.
Also solved by P. P. Dályay (Hungary), O. Kouba (Syria), J. H. Lindsey II, GCHQ Problem Solving Group
(U. K.), and the proposer.
Editorial comment. Justin S. Dyer also showed that X n /n tends to 1 almost surely as
n → ∞.
Also solved by D. Beckwith, D. F. Behan, D. Brown & J. Zerger, N. Caro (Columbia), R. Chapman (U. K.),
K. David & P. Fricano, P. J. Fitzsimmons, J. Freeman, D. Glass, N. Grivaux (France), S. J. Herschkorn,
B.-T. Iordache (Romania), J. H. Lindsey II, O. P. Lossers (Netherlands), J. & W. Matysiak (Poland), K. McIn-
turff, M. D. Meyerson, Á. Plaza & C. González-Alcón (Spain), R. Prasad (India), R. Pratt, B. Schmuland
(Canada), J. Simons (U. K.), N. C. Singer, T. Starbird, J. H. Steelman, R. Stong, S. Xiao, CMC 328, GCHQ
Problem Solving Group (U. K.), Szeged Problem Group “Fejéntaláltuka” (Hungary), and the proposer.
Also solved by D. Beckwith, N. Caro (Colombia), R. Chapman (U. K.), M. P. Cohen, P. J. Fitzsimmons,
J. Gaisser, S. J. Herschkorn, J. H. Lindsey II, K. McInturff, M. Nyenhuis (Canada), M. A. Prasad (India),
R. Pratt, K. Schilling, B. Schmuland (Canada), T. Starbird, R. Stong, and the proposers.
since Fn+1 − φ Fn = −φ . The sequence 1, 2, 1, −1, −2, −1, . . . is the sum of two
−n
sequences whose cycles are 1, −1, 1, −1, 1, −1 and 0, 3, 0, 0, −3, 0. Continuing the
computation,
∞ ∞ ∞
(−1)k+1 1 2k−1 X 3(−1)k+1 1 6k−3
2k−1 X
X ak 1
= +
k=1
2k − 1 φ k=1
2k − 1 φ k=1
6k − 3 φ
∞ ∞
(−1)k+1 1 2k−1 X (−1)k+1 1 2k−1
X
= +
k=1
2k − 1 φ k=1
2k − 1 φ 3
1 1
= arctan + arctan .
φ φ3
Using the arctangent addition formula and φ 2 = φ + 1, this becomes
1
+ φ13
!
φ +φ
3
1 1 φ
arctan + arctan = arctan = arctan
φ φ3 1 − φ1 · φ13 φ4 − 1
φ3 + φ φ +φ π
3
= arctan = arctan = arctan(1) = .
φ3 + φ2 − 1 φ3 + φ 4
for θ ∈ R and |x| < 1, from which the second part of the proof above follows with
θ = 2π/3 and x = 1/φ.
Also solved by R. Chapman (U. K.), O. Kouba (Syria), K. D. Lathrop, M. A. Prasad (India), R. Stong,
S. Y. Xiao (Canada), and GCHQ Problem Solving Group (U. K.).